ANALISIS MINAT BELI ULANG YANG DIPENGARUHI OLEH KUALITAS PRODUK, TAMPILAN IKLAN , DAN NILAI MANFAAT Pada Konsumen Spotify Di Bandar Lampung - Jonatha Agne Saputra; K Bagus Wardianto; Ghia Subagja (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2021)
Abstract This study describes the effect of Product Quality, Advertising Display, and Benefit Value on Repurchase Interest of Music Streaming Services on Spotify Consumers in Bandar Lampung. This type of research is explanatory research with a quantitative approach. The population in this study is the Spotify application consumers in Bandar Lampung. The data was obtained from an online questionnaire, the sampling technique in this study was non-probability sampling with purposive sampling technique. Data analysis in this study used descriptive analysis and multiple linear regression analysis. Based on the results of research and data analysis shows that product quality, advertising display, and benefit value simultaneously have a significant effect on repurchase interest. The results of partial testing of product quality variables have a significant effect on repurchase interest, advertising display has a significant effect on repurchase interest and the value of benefits has a significant effect on repurchase interest Keywords: Product Quality, Advertising Display, Benefit Value, Repurchasing Interest